If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + -5 = 6 Reorder the terms: -5 + 4n = 6 Solving -5 + 4n = 6 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 4n = 6 + 5 Combine like terms: -5 + 5 = 0 0 + 4n = 6 + 5 4n = 6 + 5 Combine like terms: 6 + 5 = 11 4n = 11 Divide each side by '4'. n = 2.75 Simplifying n = 2.75
| -7m-4m=22 | | 150=4(6*4)+2(6h) | | l+8=26 | | f*-2=2*-2+5 | | sin(x)=1.22 | | w-8=106 | | 5x+3=5x-10+77 | | -3(5+7x)=-40+4x | | 12+6m=7m-6(m-2) | | r+4=15 | | 0=2.4x^2+4.2x+1.2 | | 18.75+x=26.55 | | 4x-8=5x+5+75 | | 6x-2x+60= | | 2(3d-4)=2(2d+6) | | y=-3+2+5 | | (3v+5)(8+v)=0 | | 3r-18=3 | | K^2+7x=0 | | -13/5+21/2x=-29/40 | | 25(-8)= | | 2a-6+25=10a | | x+50+x+40+90=180 | | 5r+25=40 | | 6x-7=-2x-9 | | b+10=2b-20 | | bx-a=ac | | 10x=ex-28 | | v^4-13v^3+36v^2=0 | | 15*ln(1+.5x)=ln(2+15x) | | 2(2x+1)=3x-4(1-x) | | 6x+24=6x+12 |